2001
DOI: 10.1182/blood.v98.13.3757
|View full text |Cite
|
Sign up to set email alerts
|

Simian immunodeficiency virus (SIV)–specific cytotoxic T lymphocytes in gastrointestinal tissues of chronically SIV-infected rhesus monkeys

Abstract: Although systemic virus-specific cytotoxic T lymphocyte (CTL) responses are of critical importance in controlling virus replication in individuals infected with human immunodeficiency virus 1 (HIV-1), little is known about this immune response in the gastrointestinal (GI) tract. This study investigated the GI tract CTL response in a nonhuman primate model for HIV-1 infection, simian immunodeficiency virus (SIV)-infected rhesus monkeys. Lymphocytes from duodenal pinch biopsy specimens were obtained from 9 chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Indeed, several studies of rhesus macaques have demonstrated vaccine-induced functional SIV-specific CD8 T cells within the GI tract. 65,68,69 Moreover, the frequency of vaccine-induced SIV-specific CD8 T cells in the GI tract was negatively correlated with the peak viral load in plasma after challenge with the pathogenic SHIV-ku2, while there was no such correlation with the frequency of SIV-specific CD8 T cells in peripheral blood. 69 Although HIV-specific T-cell responses may reduce viral replication in vivo, the prevention of initial infection would likely require a mucosal humoral immune response.…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, several studies of rhesus macaques have demonstrated vaccine-induced functional SIV-specific CD8 T cells within the GI tract. 65,68,69 Moreover, the frequency of vaccine-induced SIV-specific CD8 T cells in the GI tract was negatively correlated with the peak viral load in plasma after challenge with the pathogenic SHIV-ku2, while there was no such correlation with the frequency of SIV-specific CD8 T cells in peripheral blood. 69 Although HIV-specific T-cell responses may reduce viral replication in vivo, the prevention of initial infection would likely require a mucosal humoral immune response.…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 81%
“…42 Studies in humans examined only the frequency of HIV-specific CD8 T cells in rectal tissue, but studies of SIV-specific CD8 T cells with peptide-major histocompatibility complex tetramers have demonstrated that SIV-specific CD8 T cells can be detected in the upper and lower small intestine. 65 However, these studies did not examine the functional capacity of HIV/SIV-specific CD8 T cells in the GI tract. Indeed, in the peripheral blood of HIV-infected individuals, some HIVspecific CD8 T cells that control viral replication and maintain peripheral blood CD4 T cells are found to produce multiple effector cytokines, including IFN-γ, macrophage-inflammatory protein-1β, TNF-α, and IL-2; they maintain the ability to degranulate (measured by surface mobilization of CD107a).…”
Section: Gastrointestinal Hiv-specific Immune Responsesmentioning
confidence: 99%
“…13,33 In addition, Mamu A01 + rhesus macaques attain significantly lower set point VLs after SIV infection compared to rhesus macaques that do not express the A01 allele, 34 and these monkeys manifest high frequencies of Mamu-A01-restricted SIV-specific CD8 T cells in both small and large intestines. [35][36][37] Moreover, Mamu-A01 + rhesus macaques that fail to control viral replication lack functional SIV-specific CD8 T cells in mucosal sites. 35 Alternatively, local HIV-specific T-cell responses in BAL may suppress viral replication by direct anti-viral effector mechanisms including cytolysis of infected cells and secretion of antiviral chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of these CTLs during chronic SIV infection in different compartments varies among animals (12). However, for the majority of chronically infected animals, the frequencies of this response are comparable in peripheral blood and lymph nodes and have often been found to be higher in the gastrointestinal and urogenital tissues, spleen, bone marrow, and liver (12,41). Here we demonstrate that in all the Mamu-A*01-positive macaques studied, larger numbers of Gag 181-189 CM9-specific CTLs could be found in the CNS than in peripheral blood (Fig.…”
mentioning
confidence: 99%
“…The levels of tetramer-binding cells with this Gag specificity in peripheral blood, spleen, lymph nodes, bone marrow, liver, and gastrointestinal and urogenital tracts of acutely and chronically SIVmac251-infected macaques have already been extensively analyzed (12,24,41,42,45). For Mamu-A*01-positive macaques, Gag 181-189 CM9 tetramerpositive CD8 ϩ T cells emerge in blood at week 2 to 3 after exposure to SIVmac251 and are found as early as 4 weeks postinoculation in secondary and tertiary lymphoid organs (13,24).…”
mentioning
confidence: 99%